Isotopic evidence for the formation of the Moon in a canonical giant impact - Sune G. Nielsen (Nature Portfolio, 2021)
Here, the authors show that Earth and Moon are characterized by different vanadium isotope compositions, which is most likely resulting from vanadium isotope fractionation of the bulk silicate proto-Earth during the main stage of terrestrial core formation—followed by a canonical giant impact scenario, where 80% of the Moon originates from an impactor of chondritic composition.